A musculoskeletal model of the lumbar spine using ArtiSynth – development and validation. Issue 5 (3rd September 2018) - Malakoutian, Masoud; Street, John; Wilke, Hans-Joachim; Stavness, Ian; Fels, Sidney; Oxland, Thomas
Abstract: A musculoskeletal model of the spine was created using ArtiSynth, an open-source biomechanical modelling toolkit. The model included the entire spine and rib cage, with the lumbar vertebrae being mobile and 210 muscle fascicles. Muscle parameters needed for a full Hill-type musculotendon model including tendon ratios and pennation angles along with muscle force-length and force-velocity curves were incorporated into the model, as were the nonlinear stiffness of the functional spinal units and the effect of intra-abdominal pressure. We used forward dynamics-assisted data tracking for the estimation of muscle forces and validated the solution method by comparing the predicted spinal forces vs. the results of two in vivo experiments in the literature. Our model produced larger maximum extension moment in flexion than extension, which is observed in in vivo experiments. These results could not be achieved without the inclusion of the muscle force-length relationship. The model was also able to predict the ratios of axial forces at L4–L5 as measured in vivo intradiscal pressures for three cases of upright standing, holding a crate close to and far from the chest. Due to the high stiffness of the spine, our solution method was sensitive to input kinematics, which hindered extensive validation of the model for body positions other than standing. Modifying the solution method, possibly by only tracking the angular motion of the vertebrae rather than their translational motion, should make the model less sensitive and enable further validation.